ANALYSIS OF THE INFLUENCE OF ROA, ROE, AND NPM ON STOCK PRICES IN THE BANKING FINANCIAL SECTOR IN 2019-2022 - Syamsiah, Erlina; Sulistiani, Rina; Aprila, Vinona Lula Putri; Septiana, Arista; Riauwanto, Selamat (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This research was conducted to determine the effect of Return On Assets, Return On Equity and Net Profit Margins on stock prices in banking sector companies in 2019-2022. Profitability is the net result of various management policies and decisions. This ratio provides an overview of the level of effectiveness of company management. Profitability is often used to measure the efficiency of the use of capital in a company by comparing profits and capital used in operations. (Sawir: 2009). The population in this study are 7 banking sector companies in 2019-2022. The sampling technique uses a purposive sampling technique so that 7 companies in the banking sector are obtained. The research method used in this study is a quantitative research method. Data analysis techniques were carried out using classical assumption tests which included normality tests, linearity tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. While hypothesis testing is done by multiple regression analysis. The results of this study are ROA, ROE and NPM partially have a significant effect on stock prices of banking sector company shares in 2019-2022 with a significant value of each ROA of 0.005 > 0.05, ROE of 0.00 > 0.05 and NPM of 0.001 > 0.05. Meanwhile, ROA, ROE and NPM simultaneously have a significant effect on the stock prices of banking sector companies in 2019-2022 with a significant value of 0.00 > 0.05.